2012
DOI: 10.1111/j.1541-1338.2012.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Building Green: Local Political Leadership Addressing Climate Change

Abstract: Municipal agreements have been instrumental in communicating commitment to addressing climate change at the local level. However, what is the practical implication of this potentially symbolic decision? This study examines the power of mayoral participation in climate change agreements in driving the proliferation of sustainable or “green” building in a city as a mechanism to reach its climate change goals. In addition, mayors can localize what is otherwise a public good by framing green buildings as having ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…However, alternative case selection methods allowing for systematic variation on these variables might produce more conclusive results. We have not explored in detail the importance of leadership from the mayor's office (Lee and Koski, 2012). Our two most active cities -Seoul and Seattle -clearly enjoyed strong leadership and proactive governments in the climate change policy sector at key points in their history.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, alternative case selection methods allowing for systematic variation on these variables might produce more conclusive results. We have not explored in detail the importance of leadership from the mayor's office (Lee and Koski, 2012). Our two most active cities -Seoul and Seattle -clearly enjoyed strong leadership and proactive governments in the climate change policy sector at key points in their history.…”
Section: Resultsmentioning
confidence: 95%
“…Table 3 both provides stylized data on the dependent variable (comprehensive climate change policies) and also indicates the level of development of urban governance arrangements. Control variables aside from national context include population; partisanship of the city government (Lee and Koski, 2012); and the strength of the environmental planning bureaucracy (Rabe, 2004). We choose the two most populous cities in Korea (Seoul and Busan) and two medium-sized American cities (Seattle and Anaheim).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a city's institutional and civic capacity (Bulkeley and Betsill 2013;Zahran et al 2008), political leadership (Lee and Koski 2012), and exposure to interest group pressure (Sharp et al 2011) have all been shown to influence whether a city adopts policies related to climate change. A growing number of quantitative studies have focused on explaining variations in the adoption of urban climate change mitigation strategies (Bart 2011;Krause 2012;Lee and Koski 2014).…”
Section: The Role Of Perceived Climate Change Hazardsmentioning
confidence: 98%
“…Participating in a translocal climate network can provide opportunities for learning and sharing ideas between cities around the world. Joining a translocal climate network is also a proxy for political leadership's commitment on the issue of local climate policies (Lee and Koski 2012). Without political leadership, a city government is not likely to participate in the network.…”
Section: Data and Analysis 41 Datamentioning
confidence: 99%